2016
DOI: 10.1371/journal.pone.0148264
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a Modifying Factor Influencing Myotonic Dystrophy Type 1 Phenotype Severity and Mortality: A Nationwide Multiple Databases Cross-Sectional Observational Study

Abstract: BackgroundMyotonic Dystrophy type 1 (DM1) is one of the most heterogeneous hereditary disease in terms of age of onset, clinical manifestations, and severity, challenging both medical management and clinical trials. The CTG expansion size is the main factor determining the age of onset although no factor can finely predict phenotype and prognosis. Differences between males and females have not been specifically reported. Our aim is to study gender impact on DM1 phenotype and severity.MethodsWe first performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 41 publications
10
104
1
4
Order By: Relevance
“…For example, the data presented support a recent study indicating gender differences in DM1 [8]. Similar to this study, men had higher frequencies of severe myotonia, mobility impairments, cardiac abnormalities, and non-invasive ventilation, whereas women presented more often with cataracts.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the data presented support a recent study indicating gender differences in DM1 [8]. Similar to this study, men had higher frequencies of severe myotonia, mobility impairments, cardiac abnormalities, and non-invasive ventilation, whereas women presented more often with cataracts.…”
Section: Discussionsupporting
confidence: 91%
“…While the reason for this gender difference is unknown, it is not surprising since gender is emerging as an important factor influencing DM1 clinical profile3031. Of note, it has been found that miR-133b stimulates ovarian estradiol synthesis32.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were recruited from 5 hospitals (National Hospital Organization [NHO] Toneyama National Hospital, NHO Okinawa National Hospital, NHO Akita National Hospital, Yokohama Rosai Hospital, and Osaka University Hospital). Although no consensus regarding the clinical classification of DM1 exists, we classified patients into 4 clinical forms according to the age at onset using criteria from a recent study; clinical onset from 1 month to 10 years of age = infantile, 11–20 years = juvenile, 21–40 years = adult, and >40 years = late onset . The number of CTG repeats was assessed by polymerase chain reaction and Southern blotting.…”
Section: Methodsmentioning
confidence: 99%